Fostering reading level and story comprehension through MARITES (Marungko Approach Reading Intervention to Elementary Schoolers) with mentor-mentee arrangement - Nancy T. Rubin; Arnel S. Travero (Northern Negros State College of Science and Technology (NONESCOST), 2022)
Developing young learners' reading level and story comprehension is fundamentally crucial as this will soon have implications as the learners go to higher grade levels. The main aim of the study is to determine how effective Marungko Approach with Mentor-Mentee Arrangement is to the reading level and story comprehension of elementary schoolers. The researchers conducted a pre-reading test among the learners and the alarming result became the basis on the conceptualization of the study. A group volunteers, who were third year Bachelor of Elementary Education (BEED) students, served as mentors to pupils and they were all oriented on how to conduct the Marungko Approach. The mentors met their mentees twice a week, on a 1-hour session. After the 6-week intervention, it was revealed that the learners have an improved reading level and story comprehension. Also, there was a rapport built by both parties. Mentors expressed their gratefulness in their early exposure to the field; while mentees stated that they now learned how to read and expressed their approval to the mentors' teaching strategies. The study recommends the use of Marungko Approach in teaching reading to elementary schoolers as it fosters learners' reading level and story comprehension. Moreover, mentoring proves to be of help during online learning. Lastly, it is highly recommended that teacher education institutions (TEIs) may ink agreements with DepEd schools to facilitate partnership and allowing their students to real-world exposure even before their internships.